Contesting Double Genealogy: Representing Rebellion Ambiguity in Babad Tanah Jawi - Fawaid, Achmad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
Since firstly written in 1612 until the âfinal versionâ in 1836, Babad Tanah Jawi had a special place among intellectual debates, partly, in regard with its âfunctionsâ as mythical genre, ancient prophecy, historical narrative of Java, genealogical prototype, and typical structure with previous texts. However, little attention was given to the fact that Mataram, largely depicted in Babad Tanah Jawi, is considered as having âproblematicâ double genealogy, which partly resulted from a double familial lineage of Batara Guru and the Prophet Adam, and the synthetic power of Demak and Majapahit. This study attempts to depict a scholarly contestation of the double genealogy of Mataram and its implication on ambivalent narratives of rebellion in the text. Â Constructed as ex post facto in the universum of historical references, Babad Tanah Jawi seemingly takes its dual position in providing a subjectively constructed cosmology of Javanese characters and in attempting to objectively illustrate historical events. In some ways, it impacts on the way the text justified Javanese rulers by providing supernatural genesis of ancestors, and âpurifyingâ genealogical defects. The result is a distorted story of those who failed and succeeded to take over the Javanese kingdoms. The ambiguity lies on the way it has to maintain mythological genealogy of rebelling descendants and to perceive such rebellion as subversive.